Immunolocalization of TGF-?2 in the rat thymus during late stages of prenatal development - Sonmez, Mehmet Fatih; Colakoglu, Neriman; Kukner, Aysel; Ozan, Enver; Dabak, Durrin Ozlem (Elsevier Gmbh, 2009)
The aim of this study was to investigate the immunolocalization of transforming growth factor beta (TGF-beta 2) in rat thymic stromal cells and thymocytes and investigate the roles of TGF-beta 2 in thymopoiesis during the late stages of fetal development. Twelve adult pregnant female Wistar rats weighing 250-270g were used in this study. The rats were killed by cervical dislocation on gestation days 16 (GD 16), 18 (GD18) and 20 (GD20). Fetal thymus glands were prepared and examined by an immunohistochemical technique to reveal binding of an anti-TGF-beta 2 rabbit polyclonal antibody. The thymic primordium was surrounded with a connective tissue capsule at GD16 and at this stage TGF-beta 2 immunoreactivity was not observed. At GD18, the connective tissue capsule had formed septa which subdivided the tissue into lobules and at this stage TGF-beta 2 immunolocalization was detected in the capsule and in thymocytes. Lobulation was more evident at GD20 and TGF-beta 2 immunoreactivity of thymocytes was more extensive than on GD18. Results indicate that TGF-beta 2 may play an important role in the organization or development of thymocytes in the late stages of thymopoiesis. (C) 2008 Elsevier GmbH. All rights reserved.
Keywords: TGF-beta 2; Thymopoiesis; Prenatal development; Thymus; Rat